FRI0268 Safety and Efficacy of Subcutaneous Tocilizumab in Early Systemic Sclerosis: Results from The Open-Label Period of The Fasscinate Trial. (15th July 2016) - Khanna, D.; Denton, C.P.; Jahreis, A.; van Laar, J.M.; Burke, L.; Spotswood, H.; Lin, C.J.; Pope, J.E.; Allanore, Y.; Müller-Ladner, U.; Siegel, J.; Furst, D.E.; et al.
Abstract : Background: Systemic sclerosis (SSc) is a debilitating disease with few treatment options. Interleukin-6 (IL-6) appears to play a role in SSc pathogenesis. 1, 2 Data from the 48-week, double-blind (DB), placebo (PBO)-controlled period of the faSScinate trial were previously presented, 3 and open-label (OL) data are presented herein. Objectives: To assess safety and efficacy of tocilizumab (TCZ) in SSc patients during 48 weeks of OL TCZ treatment. Methods: Patients ≥18 y with active SSc (≤5-year duration, modified Rodnan skin score [mRSS] 15–40, and elevated acute-phase reactants) received OL TCZ 162 mg SC weekly from week 48 to week 96. Change from baseline in mRSS, patient-reported outcomes (PROs), and FVC at week 96 were exploratory measures. Observed means used all available data. Results: In total, 27/43 (63%) TCZ and 24/44 (55%) PBO patients completed week 96. Baseline (BL) characteristics were similar at BL and at entry into the OL period. Patients who switched from PBO→OL TCZ showed improvement in observed mean change from BL in mRSS at week 96 (–9.4) relative to the end of the 48-week DB period (–3.1). In patients initially randomized to TCZ (TCZ→OL TCZ), mean change in mRSS was –5.6 at week 48 and –9.1 at week 96. In the OL period, improvements in PROs were noted at week 96 vs week 48 in the PBO→OL TCZ group (mean [SD] change from BL at week 96 vs week 48 in HAQ-DI: –0.3 [0.4] vs 0.2 [0.4]; Patient Global VAS: –23.8 [36.0] vs –4.0 [24.0]; FACIT-Fatigue:11.3 [12.8] vs 1.4 [7.6]). In patients who completed the study, none experienced a >10% decline in % predicted FVC during the OL period on TCZ therapy. Rates (95% CI) of serious adverse events/100 patient-years (PY) in the DB period were 76.1 (50.6, 110.0) in PBO patients and 66.7 (42.3, 100.1) in TCZ patients and were 36.0 (18.0, 64.4) in PBO→OL TCZ patients and 16.5 (5.4, 38.5) in TCZ→OL TCZ patients in the OL period. Rates (95% CI)/100PY of serious infections in the DB period were 10.9 (3.0, 27.9) in PBO patients and 34.8 (18.0, 60.8) in TCZ patients. In the OL period they were 19.6 (7.2, 42.7) in PBO→OL TCZ patients and 0.0 (0.0, 12.2) in TCZ→OL TCZ patients. No deaths occurred in the OL period (deaths in DB period: 3 TCZ, 1 PBO). Conclusions: Although OL data have to be interpreted with caution, efficacy and safety in PBO-treated patients who switched to OL TCZ were generally similar to those observed in patients randomized to TCZ in the DB period. Results over 96 weeks of TCZ treatment suggest maintenance of the clinical response for mRSS in SSc patients. Serious infection rates increased in PBO patients after they switched to OL TCZ. Long-term safety was consistent with the natural history of SSc and the safety profile of TCZ. References: J Rheumatol 1998;25:308. Pathobiology 1993;61:239. Ann Rheum Dis 2015;74(suppl 2):87. Disclosure of Interest: D. Khanna Grant/research support from: NIH/NIAMS, NIH/ NIAID, Bayer, BMS, Consultant for: Bayer, BMS, Genetech/Roche, GSK, Genkyotex, Sanofi-Aventis, Actelion, Gilead, C. Denton Grant/research support from: GSK, Actelion, CSL Behring, Consultant for: GSK, Bayer, Actelion, Roche, Merck-Serono, MedImmune, A. Jahreis Shareholder of: Roche, Employee of: Genentech, J. van Laar Grant/research support from: MSD, Consultant for: MSD, Roche, Pfizer, BMS, Eli Lilly, L. Burke Employee of: Roche Products Ltd., H. Spotswood Shareholder of: Roche, Employee of: Roche Products Ltd., C. Lin Shareholder of: Amgen, Roche/Genentech, Employee of: Genentech, J. Pope Grant/research support from: Roche, Bayer, BMS, Consultant for: Roche, Actelion, Bayer, BMS, Y. Allanore Grant/research support from: Bristol-Myers Squibb, Roche/Genentech, Inventiva, Pfizer, Sanofi, and Servier, Consultant for: Actelion, Bayer, Roche/Genentech, Inventiva, Medac, Pfizer, Sanofi, Servier, and UCB, U. Müller-Ladner Consultant for: Roche, Chugai Pharma, Speakers bureau: Roche, Chugai Pharma, J. Siegel Shareholder of: Roche, Employee of: Genentech, D. Furst Grant/research support from: AbbVie, Actelion, Amgen, BMS, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB, Consultant for: AbbVie, Actelion, Amgen, BMS, Cytori, Janssen, Gilead, GSK, NIH, Novartis, Pfizer, Roche/Genentech, UCB